PERCEPATAN DIVERSIFIKASI KONSUMSI PANGAN BERBASIS PANGAN LOKAL : PERSPEKTIF PEJABAT DAERAH DAN STRATEGI PENCAPAIANNYA - Drajat Martianto; Dodik Briawan; Mewa Ariani; Nita Yulianis (Jurnal Gizi dan Pangan, 2009)
Until the year of 2008, Indonesia’s food consumption quality has not met its ideal pattern yet as shown by DDP (Desirable Dietary Pattern) Score 81.9 and the domination of rice consumption up to 64.1%. The government of Indonesia’s effort to accelerate food consumption diversification requires coordination and good preparation of all related stakeholders. Therefore the aims of this study were to assess the perceptions of the key persons at the local government regarding the food consumption diversification program and to analyze the strategy priority in achieving the acceleration program. This research was carried out in March to December 2008 and used a cross sectional study. Survey was done in three provinces which represent the differences of food consumption pattern. In each province, twenty head officers at the local government purposively selected were assessed about their perception. The perception data was measured by Likert scale and analyzed by the trends using percents and mode score. The strategy priority was measured by AHP (Analytical Hierarchy Process) method. This research shows that there are variations among stakeholders in the three provinces ranging “from poor to good” in perceiving the concept and application of food consumption diversification program. Nevertheless, local food is mainly defined as should be locally produced. Increasing the commitment and participation within all stakeholders (29. 3%) are the strategy priority besides promoting local food business through capital and marketing support (25.1%).